PENERAPAN METODE REGRESI LINEAR PADA DATA PEMBELAJARAN ONLINE - Nailis Sa'adah (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Online and offline learning will not be the same. There are several differences in indicators, such as indicators of the learning process, learning quality and learning outcomes. Besides that, there is a relationship between these indicators. This research aims to examine these differences and their relationships. The research involved using associative descriptive methods using questionnaires. Respondents consisted of students at XYZ Study Program. Data analysis uses the Linear Regression Method. The research results showed that respondents assessed that learning outcome indicators tended to have the best (positive) value. Respondents agreed that learning outcomes were not too affected by differences in learning patterns. As for the relationship between indicators, indicators of the learning process and learning quality do not really influence learning outcomes